2012
DOI: 10.1002/cne.22767
|View full text |Cite
|
Sign up to set email alerts
|

Descending projections from the dysgranular zone of rat primary somatosensory cortex processing deep somatic input

Abstract: In the mammalian somatic system, peripheral inputs from cutaneous and deep receptors ascend via different subcortical channels and terminate in largely separate regions of the primary somatosensory cortex (SI). How these inputs are processed in SI and then projected back to the subcortical relay centers is critical for understanding how SI may regulate somatic information processing in the subcortex. Although it is now relatively well understood how SI cutaneous areas project to the subcortical structures, lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 99 publications
(109 reference statements)
0
18
0
Order By: Relevance
“…deed, various sources of mossy fibers, such as the dorsal column nuclei, trigeminal nuclei, lateral reticular nucleus and paramedian reticular formation have been reported to receive cortical input (Allen and Tsukahara, 1974;Lee and Kim, 2012). Although CTb-labeled cells were noted in many of these areas, their full analysis fell outside the scope of the present study.…”
Section: Role Of Extra-pontine Routesmentioning
confidence: 71%
See 1 more Smart Citation
“…deed, various sources of mossy fibers, such as the dorsal column nuclei, trigeminal nuclei, lateral reticular nucleus and paramedian reticular formation have been reported to receive cortical input (Allen and Tsukahara, 1974;Lee and Kim, 2012). Although CTb-labeled cells were noted in many of these areas, their full analysis fell outside the scope of the present study.…”
Section: Role Of Extra-pontine Routesmentioning
confidence: 71%
“…For example, it seems remarkable that climbing fiber responses in vermal lobule VII may be triggered from the prelimbic cortex (Watson et al, 2009) which does not qualify as a major disynaptic source to this region. Of course, although to some extent the cerebro-olivo-cerebellar pathway is disynaptic (Lee and Kim, 2012), it usually involves more synapses (Baker et al, 2001;Pardoe et al, 2004).…”
Section: Role Of Extra-pontine Routesmentioning
confidence: 99%
“…It is of interest that these areas are also the recipients of cerebellar input as has been demonstrated in the cat (Bull and Berkley, 1991). The IOD also receives a direct and somatotopically organized input from the somatosensory and dysgranular cortices (Swenson et al, 1989;Lee and Kim, 2012). In the rat it has been shown that the anterior interposed nucleus (IntA) of the cerebellum III.…”
Section: Afferents To the Dorsal Accessory Olivementioning
confidence: 97%
“…The homology between the situation in the cat and that in the rat has not yet been specifically investigated (see also the section below "Afferents to the principal olivary nucleus"). Direct input to the IOM has been described to originate from the sensory and supplementary motorcortices (Swenson et al, 1989;Lee and Kim, 2012). Prominent GABAergic projections arise from the contralateral IntP Fredette and Mugnaini, 1991).…”
Section: Afferents To the Medial Accessory Olivementioning
confidence: 99%
“…Here, our choice of stimulation at 10 Hz corresponds to the physiological spontaneous firing rate of TRN neurons in vivo 25, 30, 42 , noting that the effects of TRN stimulation in the current mouse model are known to be frequency-specific 2729 . With regards to a mechanistic explanation for how spatiotemporal dynamics in the thalamocortical network can alter a nociceptive spinal reflex, we note a possible role for descending corticospinal projections such as from areas 3b, 1 and 2 of SI terminating in superficial laminae I-II of the dorsal horn, as well as projections from areas 3a and 4 terminating in deeper laminae III-V 4345 . In rats, electrical stimulation in SI inhibits wide-dynamic range neurons in dorsal horn 46 , which is thought to be mediated by presynaptic inhibition of C-fiber afferents via the corticospinal tract 47, 48 .…”
Section: Introductionmentioning
confidence: 99%